(untitled) (Dimensión Empresarial, 2016)
The article analyzes consumer behavior in college students. The conceptual foundation is consumer microeconomic theory and basics of behavioral economics. Considering the statement on consumer preferences to twelve groups of goods, its analyzed the probability of realizing a monthly spending budget, taking into account their income range. We conclude that income is a key factor in developing a budget, taking into account the preferences of groups of assets. Food goods group is very important for students with income up to 2 million, while students with higher incomes have higher preferences for clothing, restaurants and hotels, and miscellaneous goods and services.